1997
DOI: 10.1042/bj3260897
|View full text |Cite
|
Sign up to set email alerts
|

Two forms of Wilson disease protein produced by alternative splicing are localized in distinct cellular compartments

Abstract: Copper is an essential trace element in prokaryotes and eukaryotes and is strictly regulated by biological mechanisms. Menkes and Wilson diseases are human disorders that arise from disruption of the normal process of copper export from the cytosol to the extracellular environment. Recently a gene for Wilson disease (WD)(also named the ATP7B gene) was cloned. This gene encodes a copper transporter of the P-type ATPase. We prepared monoclonal and polyclonal anti-(WD protein) antibodies and characterized the ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 32 publications
8
52
0
Order By: Relevance
“…This alternative splice variant has a normal read ing frame and gives rise to a shorter protein. Yang et al have shown that this protein is mainly present in the cytosol whereas the normal ATP7B is in the trans-Golgi apparatus [44]. These alternative splice variants of ATP7B are expressed in the brain [45] and could be an explanation for differences in central nervous system manifestations, as tentatively shown in this study.…”
Section: Discussionsupporting
confidence: 53%
“…This alternative splice variant has a normal read ing frame and gives rise to a shorter protein. Yang et al have shown that this protein is mainly present in the cytosol whereas the normal ATP7B is in the trans-Golgi apparatus [44]. These alternative splice variants of ATP7B are expressed in the brain [45] and could be an explanation for differences in central nervous system manifestations, as tentatively shown in this study.…”
Section: Discussionsupporting
confidence: 53%
“…The Menkes protein is a single-chain 178-kDa polypeptide that is localized to the trans-Golgi network and undergoes a copper-dependent relocalization in human and rodent cell lines (8 -10). Recent studies have revealed similar findings for the homologous Wilson disease ATPase (11,12), suggesting a common mechanism for copper transport by these proteins into the secretory pathway of the cell.…”
mentioning
confidence: 50%
“…The sections were incubated with 100-folddiluted monoclonal antibody against the NH 2 -terminal region of ATP7B, which includes the six copper-binding domains (amino acids 21 to 623; see Ref. 22) for 15 h at 4°C. After rinsing with PBS, the sections were incubated with biotinylated horse anti-mouse IgG at 1:200 with 1.5% normal horse serum for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%